DAMPAK HUKUM PEMOTONGAN UPAH PADA PERMENAKER NO. 5 TAHUN 2023 TERHADAP HAK PEKERJA DAN PEMBANGUNAN EKONOMI - Sumiyati, Sumiyati; Ratnawati, Elfrida (Ensiklopedia of Journal, 2024)
For the purpose of discussing the impact of the law on wage cuts, in the Republic of Indonesia Minister of Manpower Regulation Number 5 of 2023 on the protection of worker/labor rights and economic development, this research was conducted. Through a juridical-empirical research method approach, namely a method of approaching the implementation of normative legal rules that are connected and occur in society at every legal event. Study of documents or library materials, as well as observation, are tools used by researchers to collect data. From the research results, it shows that the implementation of the Republic of Indonesia Minister of Manpower Regulation Number 5 of 2023 has given the authority to entrepreneurs in certain labor-intensive sectors, to cut or reduce the wages of their workers/laborers, by 25% of the wages usually received, and pay them below the minimum wage standard as wages. The lowest level is the safety net, this is of course contrary to the promotion of living wages, which will have a negative impact on reducing the welfare level of workers/laborers, and of course it is contrary to the purpose of the law, as well as the purpose of economic development itself, namely realizing justice, usefulness and prosperity. , and prosperity, for society, nation and state based on Pancasila, as stated in the ideas of J.D. Mrs. Hart regarding Law and Economic Development, which must fulfill the elements: predictability, codification of objectives, procedural ability, balancing factors, accommodation, definition and clarity regarding status.Keywords: Impact of the law on wage cuts, protection of workers’/laborers’ wages, economic development.